The lowering effect of Gum Arabic on hyperlipidemia in Sudanese patients - Mohamed, Rima E.; Gadour, Mohammed O.; Adam, Ishag (Frontiers in Physiology, 2015)
Hyperlipidemia especially low density lipoprotein cholesterol (LDL-C) is a major risk factor for developing ischemic heart disease. Soluble dietary fiber has lipid lowering characteristics. Gum Arabic (GA) is 95% soluble fiber calculated on dry bases. The beneficial effect of GA on lipid profile needs further verification. A case ─ control study was conducted at Omdurman Hospital, Sudan to assess the effect of G A on serum lipids in patients with hyperlipidemia. Cases received a 20 mg tablet of atorvastatin /day plus 30 mg of GA for four weeks while the controls received atorvastatin only. Levels of lipids in serum were assessed according to conventional methods before and one month after the trial. There is no significant difference in the basic characteristics between the study and the control groups (55 patients in each arm of the study). While there was no significant difference in the levels of HDL, there was a significant reduction of the total cholesterol (25.9 vs. 7.8%, P < 0.001), triglyceride (38.2 vs. 2.9%, P < 0.001) and LDL (30.8 vs 8.1%, P< 0.001) before and after the intervention in the study compared to the controls groups.